An education model to empower women in tech entrepreneurship - Paiva, Teresa; Felgueira, Teresa; Alves, Catarina; Gomes, Natalia; Salgado, Sofia; Salaberri, Marcelo (Frontiers in Education, 2024)
This study analyses how to address the gender gap in tech entrepreneurship through an education model proposal. This proposal was grounded in Self-Determination Theory, which helps to identify the intrinsic motivation constructs needed to design an education proposal. To characterize the gender gap and especially to understand the basic needs of female students that determine their intrinsic motivation, a quantitative methodology was followed in five higher education institutions in Europe. The data collected allowed a statistical analysis focused on its description, an exploratory factor analysis, and a structural equation modelling. The results confirmed the need to explore and potentiate the intrinsic motivation of female students, particularly in their autonomy need, not forgetting the competencies and competencies. By doing so, it is possible to empower female students in their capacity to decide and choose professional paths, potentiating entrepreneurship as a relevant opportunity. By the expose, this research encompasses the Frontiers Education scope and, in particular, the scope of the Higher Education section since it contributes to improving the HEI education system in an inclusive and entrepreneurial approach.